Optimal Portfolio Formation of SRIKEHATI Index Stocks on the Indonesia Stock Exchange (2019-2023 Period) - Az-Zahra, Layalia Briliani; Viana, Eka Dasra; Kaewlaead, Chuta (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The stable economic conditions in Indonesia have had a positive impact, leading to an increase in the number of investors in the Indonesian capital market. One of the key instruments in this market is stocks. The aim of this research is to create an optimal portfolio that can be recommended to investors. The study utilizes the CAPM and Markowitz models and involves the use of secondary data. The research sample selection process makes use of non-probability sampling techniques, specifically purposive sampling. This research focuses on the SRI KEHATI Index for the period from January 2019 to December 2023. Using the CAPM method, 7 efficient stocks have been identified, namely BBCA, BBNI, BBRI, BMRI, JSMR, KLBF, and UNTR. The combination of 7 stocks using the Markowitz model forms two preferences. The first preference generates an allocation proportion with a formula that results in an annual portfolio expected return of 40.55% and an annual portfolio risk of 30.33%. The second preference generates an allocation proportion with a solver that results in an annual portfolio expected return of 46.79% and an annual portfolio risk of 32.91%.